Front Cover: Self‐Assembly of Cyclohelicate [M3L3] Triangles Over [M4L4] Squares, Despite Near‐Linear Bis‐terdentate L and Octahedral M (Chem. Eur. J. 57/2017). Issue 57 (7th August 2017) - Hogue, Ross W.; Dhers, Sébastien; Hellyer, Ryan M.; Luo, Jingwei; Hanan, Garry S.; Larsen, David S.; Garden, Anna L.; Brooker, Sally
Abstract : Simple particle counting cannot in general be reliably employed to predict the observed architecture as DFT analysis shows that vibrational contributions to entropy dominate and may significantly influence the preferred architecture. However, simple particle counting, which predicts triangles over squares, is seen to be correct here, and DFT confirms the triangles are energetically favored over the corresponding squares. Image kindly created by Michael Crawford (Dunedin). More information can be found in the Full Paper by A. L. Garden, S. Brooker et al. onpage 14193 .